Influence of age on the reactivity of the BANA test among Brazilian children. - Orrico, S. R.; de Toledo, B. E.; Fonseca, L.; Ito, I. Y. (My University, 1992)
Three hundred and twenty samples of subgingival plaque were obtained from 80 caucasian girls, ranging from 10 to 13 years of age. The samples were analyzed to verify the influence of age upon colonization of the gingival sulcus by microorganisms potentially pathogenic to the periodontal tissues. The gingival and plaque status were evaluated through the gingival index (GI) and plaque index (PlI) and the microflora was assessed by the enzymatic method benzoyl-arginine-naphthylamide (BANA). The results of the BANA test were positive for 62.50% of the tested individuals and 40% of the examined sites. The influence of age was statistically significant on BANA reactivity, and the number of positive sites was greater at 11 (57.5%) than at 12 years (28.8%).
Keywords: Benzoylarginine 2 Naphthylamide; n benzoylarginine 2 naphthylamide; adolescent; age; Brazil; chi square distribution; child; female; human; isolation and purification; metabolism; microbiological examination; microbiology; spirochete; tooth plaque; Adolescent; Age Factors; Bacteriological Techniques; Benzoylarginine-2-Naphthylamide; Chi-Square Distribution; Child; Dental Plaque; Female; Human; Spirochaetales